How should we monitor welfare in the ornamental fish trade?. (9th November 2021) - Jones, Megan; Alexander, Mhairi E.; Snellgrove, Donna; Smith, Peter; Bramhall, Sam; Carey, Peter; Henriquez, Fiona L.; McLellan, Iain; Sloman, Katherine A.
Abstract: The global ornamental fish trade is a multibillion‐dollar industry, with legal trade estimated to be worth between 15 and 20 billion per annum . Although there is existing legislation concerning the improvement of fish welfare in aquaculture and research, there is little legislation surrounding the welfare of pet fish. The different phases of the ornamental fish trade, including curation, transportation, time spent at wholesalers/retailers and time spent in domestic/public aquaria, represent different welfare concerns. Within the animal welfare field there is increasing interest in improving welfare through the creation of operational welfare indicators (OWIs), where individual indicators are aggregated to assess animal welfare. OWIs can be morphological, behavioural, physiological, metabolic or abiotic in nature, with behaviour often considered as the foremost non‐invasive method of elucidating welfare in fish. Currently, while OWIs exist for food fish species, there are no OWIs for use within the ornamental fish trade. This review looks briefly at the stressors experienced by fish within the ornamental trade, and then used a systematic approach (keywords behavio* AND fish* AND welfare) to identify relevant publications investigating existing behavioural measures of welfare used for ornamental fish species. Finally, this review considers the potential development of OWIs for the ornamental trade.